2017
DOI: 10.2527/jas.2017.1516
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid and phosphorus digestibility of fermented corn-soybean meal mixed feed with Bacillus subtilis and Enterococcus faecium fed to pigs1

Abstract: In the present study, a 2-stage solid-state fermentation process using followed by was performed with the purpose of improving the nutritional quality of corn and soybean meal (SBM) mixed feed (MF). The matrix of native MF and fermented MF (FMF) was analyzed using scanning electron microscopy to determine external structures after solid-state fermentation. Results of the present study indicated that the FMF had a greater concentration of CP and total P compared with the unfermented feed, whereas the contents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…In the present study, we found that microbial fermentation decreased crude fiber and pH value, and increased the lactic acid concentration, crude protein content and amino acid profiles of the feed. The increased crude protein after fermentation was consistent with previous fermented soybean meal (SBM) [8,25], fermented rapeseed meal [26] and fermented cottonseed meal [27]. The increase in protein may be attributed to bacterial growth and proliferation, as well as mycelia and/or enzymes produced by probiotics [28,29].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, we found that microbial fermentation decreased crude fiber and pH value, and increased the lactic acid concentration, crude protein content and amino acid profiles of the feed. The increased crude protein after fermentation was consistent with previous fermented soybean meal (SBM) [8,25], fermented rapeseed meal [26] and fermented cottonseed meal [27]. The increase in protein may be attributed to bacterial growth and proliferation, as well as mycelia and/or enzymes produced by probiotics [28,29].…”
Section: Discussionsupporting
confidence: 84%
“…Shi et al found that fermentation of rapeseed meal with Aspergillus niger increased small-sized peptides and amino acid profiles while reducing levels of neutral detergent fiber (NDF), glucosinolates, isothiocyanate and phytic acid. Fermented feed is enriched in beneficial microbiota and bacterial metabolites, which may contribute to improving the gastrointestinal microbial ecosystems of pigs [6][7][8][9][10]. Additionally, fermentation using lactic acid-producing microbes leads to a decrease in pH value of the substrates, and thus, presents beneficial effects to both the feed during storage and the animals consuming fermented products [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The fungal strain S. cerevisiae was stored in our laboratory. The fermentation process was conducted as previously described by Shi et al [ 1 ]. Briefly, each kilogram of SBM fermentation substrate was mixed with 1 L of distilled water containing 6% (v/v) B. amyloliquefaciens , 2% (v/v) L. acidophilus, and 2% (v/v) S. cerevisiae.…”
Section: Methodsmentioning
confidence: 99%
“…Soybean meal (SBM), a byproduct of oil extraction from soy seed, is the most commonly used plant protein source in the poultry and swine feed industries. However, a variety of anti-nutritional factors (ANFs) present in SBM, such as antigenic proteins, trypsin inhibitors, and oligosaccharides, interfere with digestion and absorption and have negative effects on animal health [ 1 ]. Accumulating evidence has demonstrated that microbial fermentation improves the nutritional quality of SBM by reducing the content of ANFs and increasing nutrient bioavailability [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of feed with a high content of viable desirable microorganisms increases the bioavailability of feed and improves pigs' digestibility and overall gastrointestinal functions (44), reduces the risk of diarrhea (66), and benefits pigs' health and growth performance (67). The use of fermented feed can reduce the feed cost in animal production (68). Supplementation with fermented feed increases organic acids and short-chain fatty acid concentrations in the hindgut (49) and improves intestinal functions, all of which further improve performance (69).…”
Section: Piglet Growth Performancementioning
confidence: 99%